Pathogenic Bacteria Isolated from House Flies and Compared with Pathogenic Bacteria Isolated from Children with Diarrhea - Adhim, Ridaa; Alaa Hhassein Oleiwi; Ahmed khassaf Atya (University of Thi-Qar Journal of Science, 2023)
House flies carry many disease-causing bacteria. Through this study, we will find the relationship between house flies and bacteria that cause diarrhea in children. A total of three hundred and fifty flies were collected from (butchers, chicken and fish shops, markets, house and hospitals) and 200 samples were collected from children with diarrhea from each of Shatrah and Nasiriyah Governorate during the research period from July 2022 to January 2023 in Thi-Qar Governorate. The current study showed that 126 (36.0 %) of the flies carried bacteria, while 224 (64.0 %) of them did not contain bacteria. The current study showed that the percentage of high isolated bacteria was from the internal content of flies (8.71%), followed by(5.57%), on the external surface of flies. the present study showed the high isolated bacteria were from butcher (4.29%), following in hospital (4.0%),while the lowest isolated bacteria from flies collected from houses( 2.86%), The current study showed that the most isolated bacteria is E. coli with a percentage of( 24.3%), followed by S. aureus (17.0%), followed by Klebsiella. spp (13.15%), while the least isolated bacteria is Micrococcus (3.94%).When comparing the bacteria present in flies with the bacteria isolated from pediatric patients with diarrhea, these bacteria, the current study showed that the predominant bacteria was Escherichia coli from diarrhea with a percentage of (44.63%), and Escherichia coli was (36.27%) in the dominant flies. Staphylococcus aureus in flies followed (25.49%)